DISPENSASI NIKAH BERDASARKAN UNDANG-UNDANG NOMOR 16 TAHUN 2019 PADA PENGADILAN AGAMA TAKALAR - Abdul Mujib Sawihi; Muh. Saleh Ridwan; Muh. Jamal Jamil (Universitas Islam Negeri Alauddin Makassar, 2023)
This research examines the problem regarding applications for marriage dispensation for minors according to Law Number 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning Marriage at the Takalar Religious Court and explores the reasons judges grant marriage dispensation and the impact it has. This research includes the type of qualitative research that is descriptive analysis. From the results of the study, it can be concluded that all the reasons and actions taken by the applicant's parents can be prevented by the judge in giving legal considerations or decisions. This is where the role of the judge must be more thorough in viewing cases, making decisions, and providing advice so that child marriage does not happen and is given an understanding to wait until the time is in accordance with Law No. 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning marriage, where in Article 7 paragraph (1), men and women can marry if each is of age 19 years old..